Avaliação das alterações do fluido crevicular gengival drenado de tecidos gengivais clinicamente normais submetidos à laser em baixa intensidade: estudo em anima nóbile - Livio de Barros Silveira (2008)
In periodontology the gingival tissue, peripheral blood flow and crevicular gingival fluid (which normally comes out of the gingival socket) are the most important immune barriers acting as defense mechanisms at the front door for peridontal disease. The purpose of this study is to present a non invasive and safe activation of the immune system during the beginning process of periodontal disease associated to dental plaque, by stimulating the gingival tissue through low intensity laser at two different waves lengths and observing the changes in the gingival crevicular fluid drained from normal gingival tissues. Thirty volunteers were selected for this study, with ages between 18 and 60 years old, with clinically normal dental and periodontal structures. Six frontal interdental gingival areas were selected from each patient being 3 areas at the jawbone and 3 areas at the mandible. At the jawbone, one area did not receive any kind of radiation, one area was submitted to low intensity laser irradiation of . = 780 nm and one area submitted to laser irradiation of . = 680 nm. The same procedure was repeated for the mandible. The protocol used 40mW of power (spot area of 0,04 cm2) for the different types of laser, with irradiation time of two and a half minutes resulting on a dose of 150 J/cm2. The changes of the gingival tissues after the laser irradiation with 2 different wave lengths where observed and analyzed: the cellular components of the gingival crevicular fluid (neutrophils and macrophages) the volume change of the fluid measured by Periotron and temperature variations (due to the increase of the blood flow) registered by a thermocamera. Based on the results we can conclude that: about variations of volume and cellular presence, the lasers of low intensity emission infrared (. = 780 nm) and red (. = 680 nm), at the conditions of the present study, promoted an increase of the drained gingival crevicular fluid and an increase of number of macrophages present in its composition, but only the red laser promoted a decrease of the neutrophils present in its composition. The temperature variation tests indicated that the use of the low intensity laser on the gingival tissues caused and average change of only 0,5º C, not causing thermal damage.Key words: Low Level Laser intensity, gingival